Development of smartphone apps for serial assessment of wounds and scars, and aesthetic surgery : image processing - Ling, Li Audrey (2018)
Over the years wound assessment have been a topic of research and study for healthcare practitioners. Wound analysis is solely dependent on the colours and exposed surface area of the wound. This poses many challenges to healthcare practitioners as how individual perceive colours varies. Hence, analysis of the severity and condition of wounds might be affected by subjective judgement from healthcare practitioners. In turn, serial wound assessment too is exposed to subjectivity as subsequent wound assessment is based on the recall of previous assessment. This project concentrates in the development of digital image processing methods to address the challenges healthcare practitioners face in wound assessment and assist them in analysing and monitoring of wounds through an android application. This report documents the work done and areas researched upon for existing project on the development of a smartphone application on the serial assessment of wounds and scars, WoundAnalyser v.01. In the current version of WoundAnalyser v.1, possible techniques of digital image processing are investigated. In addition, ways to enhance usability are also explored with new features added into WoundAnalyser v.1.The methods and techniques explored will also be illustrated in this report. WoundAnalyser v.1, with the improvement on usability and added functions with the digital image processing techniques, can be used by diabetic’s patients who required serial wound assessment for chronic wounds. Besides the capability for wound monitoring, WoundAnalyser v.1 can be extended to scar monitoring for aesthetic purposes.